Spa kaki dengan Bantuan Kayu Refleksi terhadap Saturasi Oksigen pada Diabetesi - I Made Sukarja; I Wayan Sukawana (Jurnal Gema Keperawatan, 2020)
Chronic hyperglycolia in people with diabetes results in changes in intra-cell biochemical homeostasis so that the selendothel and nerves are disturbed. Disorders of blood vessels and nerves result in decreased blood supply to the legs. Decreased blood supply to the legs is characterized by a decrease in the value of oxygen saturation. Efforts are needed to improve oxygen saturation in people with diabetes to prevent diabetic foot disease. The purpose of this study was to determine the effect of Foot SPA with the help of wood reflection on oxygen saturation in people with diabetes in South Denpasar. The study was conducted with a quasi-experimental method, pre-test post test with control group design. The study used 2 (two) groups, group I was given treatment in the form of Foot SPA with the help of wood reflection every 2 days 15-30 minutes for 6 weeks, group II (control group) were given foot exercises every 2 days 15-30 minutes for 6 weeks. Saturation data were collected with digital oximetry at the beginning of the study and one day after the treatment period ended. Data were analyzed by paired and unpaired different tests. The results of the statistical independent test of the t test that have been done show that the value of p value is 0,000 (p value 0.05). This shows that there is a significant difference in oxygen saturation of the legs in the diabetics between the treatment groups that are given SPA reflective wooden foot SPA with a control group that is only given diabetic foot exercises. This can also be seen from the difference in the average oxygen saturation of the feet with diabetes in the treatment group by 4.52% and the control group by 0.28%. The results of the analysis showed that the administration of reflex wooden aids on foot was more effective in increasing oxygen saturation of the feet compared to only foot exercises in the control group.